{[(N-Butyl-N-methylcarbamothioyl)sulfanyl]acetato-kappa O}tris(2-chlorobenzyl)tin(IV) - Keng, T.C.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The Sn atom in the title compound, [Sn(C7H6Cl)(3)(C8H14NO2S2)], is coordinated by three chlorobenzyl ligands and one carboxylate O atom of the substituted acetate ligand in a distorted tetrahedral environment. Three of the C atoms of the n-butyl group are disordered over two sites with equal occupancies.